The importance of customer trust toward ewom on customer behavior: The case of generation y in Indonesia - Elia Ardyan; Christina Sudyasjayanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This study determines the effects of customer trust towards eWOM on customer behavior. This study focuses on Generation Y in Indonesia. The samplesof this study are about 260 respondents who have used eWOM. This study uses structural equation modelling (SEM) to analyze data. The results of this study indicate that trust can mediate the customer experience toward eWOM on customer behavior. The attractiveness of eWOM itself strongly influences customer trust toward eWOM. Other results also show the critical role of customer trust towards eWOM indirectly improving customer behavior.